Quantitative duplex real-time polymerase chain reaction assay with TaqMan probe detects and quantifies Crocodylus porosus in food chain and traditional medicines - Ahmad Nizar, Nina Naquiah; Hossain, Motalib; Sultana, Sharmin; Ahamad, Mohamad Nasiruddin; Johan, Mohd Rafie; Ali, Md. Eaqub (Taylor & Francis, 2019)
Consumption and exploitation of crocodiles have been rampant for their exotic, nutritive and medicinal attributes. These depredations are alarming and although they have continued to be monitored by wildlife and conservation agencies, unlawful trading of crocodiles shows an increasing trend worldwide. Recently, conventional polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism (RFLP) assays for crocodile have been documented but they are only suitable for identification and cannot quantify adulterations. We described here a quantitative duplex real-time PCR assay with probes to quantify contributions from Crocodylus porosus materials simultaneously. A very short amplicon size of 127bp was used because longer targets could have been broken down in samples, bringing considerable uncertainty in molecular analysis. We have validated a TaqMan probe-based duplex real-time PCR (qPCR) assay for the detection of 0.004 ng DNA in pure state and 0.1% target meat in model chicken meatball. False negative detection was eliminated through an endogenous control (141-bp site of eukaryotic 18S rRNA). Analysis of 12 model chicken meatballs adulterated with C. porosus reflected 96.3−120.2% target recovery at 0.1−10% adulterations. A validation test of 21 commercial food and traditional medicine (TM) crocodile-based products showed 100% effectiveness. Short amplicon sizes, alternative complementary target, exceptional stability and superior sensitivity suggested the assay could be used for the identification and quantitative determination of C. porosus in any food or TM samples even under degraded conditions. © 2019, © 2019 Taylor & Francis Group, LLC.